Combined Effect of Incentive Spirometry and Diaphragmatic Exercise on Respiratory Outcomes Post Upper Abdominal Surgery: A Literature Review - Christo Ajai, Siluvai S; Karishma, Chauhan; Jeffery, Samuel (INTI International University, 2025)
Background: Upper abdominal operations mainly cause respiratory complications because the incision across the abdominal region reflects in decreased diaphragmatic movement , e.g., atelectasis and pneumonia. Incentive spirometry (IS) and diaphragmatic breathing exercises (DBE) are the most employed interventions to enhance lung function and minimize these complications. Although each of these has been demonstrated with positive results individually, their interactive effects on respiratory recovery after surgery are not fully understood. The present literature review investigates the synergy between IS and DBE in respiratory outcomes after upper abdominal surgery, particularly concerning lung volumes, oxygenation, and minimizing postoperative pulmonary complications. Objective: This review aims to evaluate the combined effect of incentive spirometry and diaphragmatic exercise on improving respiratory outcomes in individuals recovering from upper abdominal surgery. Methods: A web-based literature search was conducted using PubMed to identify studies on the combined effects of incentive spirometry and Diaphragmatic exercises. The search focused on their impact on peak expiratory flow rate, breathing patterns, and chest expansion in post-operative upper abdominal surgery patients. Titles and abstracts were screened, and relevant articles were included. Additionally, secondary searching was performed by reviewing reference lists for relevant citations. Result: The review suggests that incentive spirometry and diaphragmatic exercises impact Respiratory outcomes i.e. PEAK EXPIRATORY FLOW RATE, breathing patterns, and chest expansion. However, the combined approach appears more effective, as mean differences indicate. This highlights the potential benefits of integrating incentive spirometry and diaphragmatic exercises in postoperative care. Conclusion: The review indicates that incentive spirometry and diaphragmatic exercises enhance respiratory outcomes in individuals recovering from upper abdominal surgery.